The Internalization of Qur'anic Values through a Psycholinguistic Approach in Islamic Education Lessons at Tsurayya Islamic School Malang - Ismail Ubaidillah (JIPI (Jurnal Ilmiah Pendidikan Islam), 2026)
Current Islamic Religious Education (PAI) learning often shows a tendency towards pedagogical reductionism that is only oriented towards cognitive aspects and textual memorization, thus creating a gap between text understanding and authentic appreciation of values. This study aims to analyze the process of internalizing Qur'anic values through a psycholinguistic approach in seventh-grade students at Tsurayya Islamic School Malang, the role of this approach in facilitating mental processing, and its implications for the formation of religious character. The method used is a qualitative approach with a case study design. Data were collected through participant observation, in-depth interviews, and documentation, which were then analyzed using the interactive model of Miles, Huberman, and Saldana as well as thematic analysis. The research instrument focused on indicators of cognitive processes such as meaning construction and affective dimensions such as emotional resonance. The results show that the internalization of Qur'anic values is a multidimensional phenomenon involving the continuous integration of cognitive, affective, and action aspects. The psycholinguistic approach has been proven to act as a bridging framework that connects the text of revelation with the construction of mental meaning through the stages of linguistic perception, decoding , and meaning integration. Reflective activities and the interpretation of the language of the Quran can trigger emotional engagement that strengthens the retention of values in students' long-term memory. In conclusion, the integration of linguistic, cognitive, and affective dimensions in Islamic Religious Education (PAI) learning can produce a stable and tangible transformation of religious character in everyday behavior. The success of this internalization depends heavily on pedagogical strategies that can orchestrate conceptual understanding with meaningful spiritual experiences.